Analysis of Water Environment Quality Around Cikundul Landfill In Sukabumi City - Risa Salsabila; Eneng Rahmi; Utamy Sukmayu Saputri; Nita Kurnita Sari (Nusa Putra University, 2024)
Landfills are potential sources of water pollution from waste. Therefore, it is necessary to conduct research related to the quality of the aquatic environment around the Cikundul landfill in Sukabumi City to overcome the problem of water pollution. This research will be conducted in the Cikundul landfill environment with a focus only on the aquatic environment around the landfill. The method used in this research is descriptive qualitative. In this study, the subject of research is the quality of the aquatic environment around the Cikundul landfill in Sukabumi City. Meanwhile, the object of research is the Cikundul landfill in Sukabumi City. The results showed that the leachate water quality in Cikundul landfill for the last 3 years had TSS concentrations ranging from 100 - 548 mg/L, COD concentrations ranging from 106 - 1979 mg/L, BOD concentrations ranging from 35 - 171.3 mg/L. There was a decrease in water quality in the Lower Cipanegah and Lower Cimandiri rivers. This condition is thought to be due to the discharge of leachate that exceeds the quality standards into public waters and the habit of people around the river who dispose of their domestic waste directly.